Sensorimotor gating and spatial learning in α7‐nicotinic receptor knockout mice. (10th April 2013) - Azzopardi, E.; Typlt, M.; Jenkins, B.; Schmid, S.
Abstract : The role of acetylcholine and specific nicotinic receptors in sensorimotor gating and higher cognitive function has been controversial. Here, we used a commercially available mouse with a null mutation in the Chrna7 tm1Bay gene [α7‐nicotinic acetylcholine receptor (nAChR) knockout (KO) mouse] in order to assess the role of the α7‐nAChR in sensorimotor gating and spatial learning. We examined prepulse inhibition (PPI) of startle and nicotine‐induced enhancement of PPI. We also tested short‐ and long‐term habituation of the startle response as well as of locomotor behaviour in order to differentiate the role of this receptor in the habituation of evoked behaviour (startle) vs. motivated behaviour (locomotion). To address higher cognition, mice were also tested in a spatial learning task. Our results showed a mild but consistent PPI deficit in α7‐nAChR KO mice. Furthermore, they did not show nicotine‐induced enhancement of startle or PPI. Short‐ and long‐term habituation was normal in KO mice for both types of behaviours, evoked or motivated, and they also showed normal learning and memory in the Barnes maze. Thorough analysis of the behavioural data indicated a slightly higher degree of anxiety in α7‐nAChR KO mice; however, this could only be partially confirmed in an elevated plus maze test. In summary, our data suggest that α7‐nAChRs play a minor role in PPI, but seem to mediate nicotine‐induced PPI enhancement. We found no evidence to suggest that they are important for habituation or spatial learning . Abstract : Commercially available knockout (KO) mouse for the α7‐nicotinic receptor was used to evaluate its role in sensory filtering [habituation and prepulse inhibition (PPI) of startle, and habituation in the locomotor box], nicotine‐enhanced sensorimotor gating and in spatial learning. Mice showed normal habituation. In contrast to previous reports, a mild but very consistent impairment of PPI was observed in these mice. Most importantly, nicotine‐enhanced PPI was absent in KO animals, suggesting a crucial role of the α7‐nicotinic receptor in enhancing PPI by nicotine. Spatial learning was unperturbed in these animals; however, we found some evidence for a slightly increased anxiety level.